By the River Piedra I sat down and wept - Coelho, Paulo (Thorsons, 2014)
Rarely does adolescent love reach its full potential, but what happens when two young lovers reunite after eleven years? Time has transformed Pilar into a strong and independent woman, while her devoted childhood friend has grown into a handsome and charismatic spiritual leader. She has learned well how to bury her feelings . . . and he has turned to religion as a refuge from his raging inner conflicts.Now they are together once again, embarking on a journey fraught with difficulties, as long-buried demons of blame and resentment resurface after more than a decade. But in a small village in the French Pyrenees, by the waters of the River Piedra, a most special relationship will be reexamined in the dazzling light of some of life's biggest questions.